Sustainability in a Sand-Depleted World: Identifying Barriers to Adoption of Sand Substitutes - Zadeh, Adel A.; Peng, Yunxin; Puffer, Sheila M. (European Journal of Sustainable Development, 2023)
The global sand crisis has gained considerable attention among environmentalists over the last few years, and the United Nations has proposed some initiatives to reduce the use of river sand. Despite the existence of a number of promising sustainable alternatives to alluvial sand, there has been little effort to implement those initiatives in the construction industry. This paper attempts to develop a better understanding of barriers and challenges related to the adoption of sustainable substitutes for sand in the construction industry. An online survey designed by the authors was distributed among construction industry professionals located in 35 US states and 7 Canadian provinces. The findings from 344 respondents show that different stakeholders in construction have different priorities and concerns when it comes to sustainable sand substitutes, with some focusing more on the technical and practical aspects, while others focus more on the long-term and environmental aspects. Keywords: : Construction industry, sand crisis, barriers, awareness, sand substitutes